Pengaruh Model Pembelajaran RQA (Reading, Questioning Dan Answering) Terhadap Pemahaman Konsep IPA Siswa Kelas V SD Muhammadiyah 02 Cimanggu - Isnawati, Pebri; Estiwi, Enggar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of the RQA (Reading, Questioning, and Answering) learning model on the science concept comprehension of fifth-grade students at SD Muhammadiyah 02 Cimanggu. The research method used is pre-experimental with a One Group Pretest-Posttest design involving 24 students. Data collection was carried out through tests, observations, and documentation, with tests as the main instrument. Data analysis used a quantitative approach through comparison of pretest and posttest, followed by normality test, homogeneity test, and paired samples t-test at a 5% significance level. The results show that the average posttest score of 72.0286 is higher compared to the pretest score of 64.3216. The hypothesis test using a paired samples t-test at a 5% significance level yielded a sig. value of 0.016, which is smaller than 0.05. This indicates that the RQA (Reading, Questioning, and Answering) learning model has a significant effect on improving the science concept understanding of fifth-grade students at SD Muhammadiyah 02 Cimanggu. This study has limitations in the use of a design without a control group, a limited number of subjects, and a relatively short research duration. Therefore, it is recommended that future research involve a larger sample, use a stronger experimental design, and extend the research duration so that the results obtained are more comprehensive and generalizable.